The relationship between infertility stress, coping, and quality of life among women undergoing infertility treatment - Büşra Çark; Seyhan Çankaya; Ümmügülsüm Esenkaya (Anatolian Journal of Health Research, 2026)
Aim: This study aimed to examine the relationships between infertility-related stress, coping strategies, and quality of life among women undergoing infertility treatment. Methods: This descriptive, cross-sectional study was conducted between April-November 2025 with 200 women attending an infertility outpatient clinic at a city hospital in Central Anatolia, Türkiye. Data were collected using a Personal Information Form, the COMPI Fertility Problem Stress Scales, the COMPI Coping Strategy Scales, and the Fertility Quality of Life Questionnaire (FertiQoL). Data were analyzed using independent samples t-tests, one-way ANOVA, Pearson correlation analysis, and multiple linear regression analysis. Results: The participants’ mean age was 31.6±3.3 years, mean marriage duration 8.3±3.3 years, mean infertility duration 3.8±2.3 years, and mean treatment duration 3.1±1.4 years. FertiQoL core, treatment, and total scores were lower among women who were unemployed, smokers, had spouses with lower educational levels, had infertility attributed to both partners, were undergoing IVF/IUI treatment, had never been pregnant, or had a history of pregnancy after treatment (p